Mechanical and Durability Properties of Polyvinyl Alcohol (PVA) Treated Oil Palm Shell (OPS) Lightweight Concrete - Thong, Chia Chia (unimas, 2016)
This study investigated the mechanical and durability properties of lightweight concrete containing polyvinyl alcohol (PVA) treated oil palm shell (OPS) aggregates under different curing conditions. 5% PVA solution which was found to be the optimum concentration was used to the OPS aggregates before concrete mixing to produce PVA treated OPS concrete. The tests conducted to assess the mechanical properties of PVA treated OPS concrete were compressive strength, tensile splitting strength and flexural strength. For durability tests, the water absorption, volume of permeable voids (VPV), sorptivity, 90-day salt ponding and the silver nitrate colourimetric of PVA treated OPS concrete were examined. Three types of curing conditions were employed in this study to determine its effect on the mechanical and durability properties of PVA treated OPS concrete. All results obtained were analysed and a comparison were made between the PVA treated OPS concrete and raw OPS concrete. The implementation of PVA treated OPS aggregates in concrete production did not only contribute to an improvement in the mechanical properties, but also decreases the value of VPV and improves the resistance to absorption and chloride-ion penetration of the concrete. In terms of curing conditions, PVA treated OPS concrete under air-drying condition was found to gives higher percentage improvement in water absorption, sorptivity and chloride penetration as compared to the others types of curing conditions.